Drought stress mitigation through bioengineering of microbes and crop varieties for sustainable agriculture and food security - Satish Kumar; Satyavir Singh Sindhu (Current Research in Microbial Sciences)
Climate change and agriculture are intrinsically connected and sudden changes in climatic conditions adversely impact global food production and security. The climate change-linked abiotic stressors like drought and high temperatures are resulting in crop failure. The most severe abiotic stress drought significantly affect the stomatal closure, production of reactive oxygen species, transpiration, photosynthesis or other physiological processes and plant morphology, and adversely affect plant growth and crop yield. Therefore, there is an exigent need for cost effective and eco-friendly modern technologies to induce drought tolerance in crop plants leading to climate-adapted sustainable agricultural practices for sustained food production. Among many options being pursued in this regard, the use of plant growth promoting microbes (PGPMs) is the most sustainable approach to promote drought stress resilience in crop plants leading to better plant growth and crop productivity. These PGPMs confer drought resistance via various direct or indirect mechanisms including production of antioxidants, enzymes, exopolysaccharides, modulation of phytohormones level, osmotic adjustment by inducing the accumulation of sugars, along with increases in nutrients, water uptake and photosynthetic pigments. However, several technological and ecological challenges limit their use in agriculture and sometimes treatment with plant beneficial microbes fails to produce desired results under field conditions. Thus, development of synthetic microbial communities or host mediated microbiome engineering or development of transgenic plants with the capacity to express desired traits may promote plant survival and growth under drought stress conditions. The present review critically assesses research evidence on the plant growth and stress resilience promoting potentials of PGPMs and their genes as an approach to develop drought resilient plants leading to increased crop productivity. Effective collaboration among scientific communities, policymakers and regulatory agencies is needed to create strong frameworks that both promote and regulate the utilization of synthetic microbial communities and transgenic plants in agriculture.